Illegal Acts in Business Versus Criminal Acts : A Comparative Study - Fernando, Youngky (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to explain the differences between illegal acts (PMH) in civil law and criminal law, along with the elements that distinguish the two. It discusses examples of illegal acts in the context of business and criminal law, as well as the legal implications of these actions. The research method used is normative juridical research, which focuses on the analysis and interpretation of applicable laws. Data collection techniques include documentary studies, analyzing and interpreting primary, secondary, and tertiary legal materials, as well as literature review, examining books, articles, and journals related to the research topic. Data analysis involves analyzing and interpreting the relevant laws regarding illegal acts in both business and criminal law and comparing these illegal acts within the context of Indonesian law. The findings indicate that illegal acts in business and criminal law have several fundamental differences. In civil law, illegal acts are defined under Article 1365 of the Civil Code, where the harmed party has the right to claim compensation. The primary difference between illegal acts in civil law and criminal law lies in the nature and objectives of the acts. In civil law, illegal acts focus more on compensation and restitution for the harmed party, while in criminal law, the focus is on punishment and preventing unlawful actions. Examples of illegal acts in business may involve violations of intellectual property rights or other regulatory breaches, whereas in criminal law, illegal acts include crimes such as theft, fraud, or other violations of criminal law